LONDOÑO SULKIN, Carlos. 2012. People of Substance: An Ethnography of Morality in the Colombian Amazon. Toronto/ Buffalo/ London. University of Toronto Press. 240.pp - Pérez Gil, Laura (Campos - Revista de Antropologia, 2014)
Resenha do livro People of Substance: An Ethnography of Morality in the Colombian Amazon, de Carlos Londoño Sulkin, publicado em 2012.